THE IMPACT OF SOCIAL MEDIA ON THE RUSSIAN LANGUAGE: DYNAMICS, TRANSFORMATIONS, AND DEVELOPMENT PROSPECTS (Eureka Journal of Education & Learning Technologies, 2026)
This article examines the complex impact of social media on the modern Russian language in the context of digitalization and globalization of the information space. It analyzes the lexical, word-formation, morphological, syntactic, stylistic, and pragmatic changes occurring in the language under the influence of online communication. Particular attention is paid to the phenomenon of digital discourse, linguistic economy, the transformation of written language norms, and the relationship between literary language and online communication. It concludes that social media has a contradictory influence: while they simultaneously promote linguistic creativity and the development of new communication strategies, they also pose the risk of declining speech standards.
Keywords: Russian language, social networks, internet discourse, digital communication, language norm, neologism, anglitsism, speech culture